Quantification of the inherent radiopacity of glass microspheres for precision dosimetry in yttrium-90 radioembolization. (23rd August 2019) - Henry, E Courtney; Mawko, George; Tonkopi, Elena; Frampton, John; Kehoe, Sharon; Boyd, Daniel; Abraham, Robert; Gregoire, Marc; O'Connell, Kathleen; Kappadath, S Cheenu; Syme, Alasdair
Abstract: Introduction:Transarterial radioembolization is a treatment for nonresectable, hypervascular liver tumours where yttrium-90-infused microspheres are administered through the arterial vasculature of the liver to selectively target liver tumours. Compared to conventional PET and SPECT imaging, post-procedural CT imaging has the potential to provide superior spatial resolution imaging of microsphere distributions and improve dosimetry estimates. In this paper, we describe a methodology to quantify the inherent radiopacity of glass microspheres using CT. This methodology produces a calibration curve that relates microsphere concentration within a CT voxel to the corresponding change of Hounsfield unit for that voxel. Methods: The radiopaque microspheres under investigation are composed of proprietery blends of yttrium-strontium-gallium-silicate oxide glass similar in size and density to TheraSphere ® microspheres. Tissue-equivalent phantoms were designed to determine CT voxel enhancement from uniformly distributed microspheres. Phantoms were imaged with a 128-slice CT scanner to determine the average Hounsfield unit value and with brightfield microscopy to determine the corresponding microsphere concentrations. Results: Hounsfield units (HU) and microsphere concentration (MS/mL) are positively correlated (r 2 ≥ 0.930) over a range of CT acquisition parameters. Calibration curve slopes (sensitivities) range from 2.22 × 10 −4 to 3.12 × 10 −4 HU/MS/ml. Minimum detectable limits are between 1.83 × 10 5 and 2.54 × 10 5 MS mL −1 . The application of this proposed methodology to recently developed microsphere formulations shows an improvement in correlation (r 2 ≥ 0.995), sensitivity (7.53 × 10 −4 HU/MS/ml), and minimum detectability (5.39 × 10 4 MS ml −1 ). Conclusion: CT has the potential to quantify the radiation dose from the infusion of microspheres for more accurate dosimetry in radioembolization. This finding may improve our understanding of the relationship between absorbed dose and tumour response, which could ultimately translate into improved patient outcomes. Optimization of the prototype microsphere composition to maximize its inherent radiopacity will be an important step in realizing this goal.